Seasonal Dynamics, Longevity, and Biting Activity of Anopheline Mosquitoes in Southwestern Ethiopia. Issue 1 (21st January 2016) - Taye, Behailu; Lelisa, Kidane; Emana, Daniel; Asale, Abebe; Yewhalaw, Delenasaw
Abstract: Continuous monitoring of vector species composition, abundance, dynamics, feeding pattern, and host finding strategy is the base to determine when, what, and how control should be implemented. Thus, this study was conducted to assess entomological parameters of anopheline mosquitoes in nine villages in Seka district, southwestern Ethiopia, from June to December 2012. Mosquito collection was carried out from selected households in each of the nine study villages using light trap catches from June to December 2012. Differences in mean mosquito density, parity rates before, and after indoor residual spraying (IRS) operation were compared. In total, 1, 136 adult female anopheline mosquitoes were collected during the study period. All anopheline mosquitoes collected belong to three species. Anopheles gambiae senso lato Giles was the most predominant (69.7%) followed by Anopheles coustani s.l. Laveran (22.7%) and Anopheles pharoensis Theobald (7.6%). There was significant variation in mean mosquito density among An. gambiae s.l., An. coustani s.l., and An. pharoensis . Parity rate of An. gambiae s.l. before spray operation was significantly higher than after spray operation. The highest peak biting activity of An. gambiae s.l. was between 1800 and 2100 hours. The longevity of An. gambiae s.l. ranged from 3.4 to 12.5 d. The highest vector abundance and parity rate were recorded in July and August. In conclusion, the behavioral plasticity and early biting activity of An. gambiae s.l. could affect current vector control tools (IRS and long lasting insecticidal nets). Hence, it is imperative to explore intervention tools for outdoor malaria vector control in addition to the existing IRS and long-lasting insecticidal nets.